Respuesta :
Set up the composite result function.
g
(
f
(
x
)
)
g
(
f
(
x
)
)
Evaluate
g
(
f
(
x
)
)
g
(
f
(
x
)
)
by substituting in the value of
f
f
into
g
g
.
g
(
x
+
2
)
=
3
(
x
+
2
)
2
−
5
(
x
+
2
)
−
2
g
(
x
+
2
)
=
3
(
x
+
2
)
2
-
5
(
x
+
2
)
-
2
Simplify each term.
g
(
x
+
2
)
=
3
x
2
+
12
x
+
12
−
5
x
−
10
−
2
g
(
x
+
2
)
=
3
x
2
+
12
x
+
12
-
5
x
-
10
-
2
Simplify by adding terms.
g
(
x
+
2
)
=
3
x
2
+
7
x
g
(
f
(
x
)
)
g
(
f
(
x
)
)
Evaluate
g
(
f
(
x
)
)
g
(
f
(
x
)
)
by substituting in the value of
f
f
into
g
g
.
g
(
x
+
2
)
=
3
(
x
+
2
)
2
−
5
(
x
+
2
)
−
2
g
(
x
+
2
)
=
3
(
x
+
2
)
2
-
5
(
x
+
2
)
-
2
Simplify each term.
g
(
x
+
2
)
=
3
x
2
+
12
x
+
12
−
5
x
−
10
−
2
g
(
x
+
2
)
=
3
x
2
+
12
x
+
12
-
5
x
-
10
-
2
Simplify by adding terms.
g
(
x
+
2
)
=
3
x
2
+
7
x